Shear band evolution related with thermal annealing revealing ductile-brittle transition of Zr35Ti30Be27.5Cu7.5 metallic glass under complex stress state. (January 2022) - Liu, Xiangkui; Wang, Tianchi; Wang, Qipeng; Song, Xinxiang; Liang, Yuzheng; Feng, Shuai; Yang, Feng; Chen, Xinsheng; Kong, Jian
Abstract: The ductile-brittle transition (DBT) caused by thermal annealing was systematically investigated by means of small punch test (SPT), accompanied by finite element simulation, uniaxial compression and nanoindentation in Zr-based metallic glasses (MGs) annealed for 1 h in a wide temperature range, i.e., sub-Tg, Tg ∼ Tx and above-Tx . In multiaxial loading mode, three deformation mechanisms, i.e., (ⅰ) circumferential shear bands (CSBs) + radial shear bands (RSBs), (ⅱ) RSBs and (ⅲ) radial cracks (RCs), can be found separately on MGs annealed sub-Tg, Tg ∼ Tx and above-Tx, leading to a transition in deformation mode from ductility to brittleness. First, for MGs with sub-Tg, Tg ∼ Tx annealing, the reduction in the number of CSBs and RSBs, as well as the disappearance of CSBs, are responsible for the ductile-brittle transition, which is attributed to the annihilation of free volume caused by structural relaxation and the reduction of released elastic energy. Based on simulation results, the decrease in plasticity of MGs is accompanied by the reduction in stress distribution area, which is in agreement with the change in the number and distribution area of shear bands. The initiation of multiple shear bands and their strong interaction dramatically improve the plasticity of MGs under the synergistic effect of large stress distribution area and high content of free volume. Second, the embrittlement of MGs with above-Tx annealing is mainly attributed to the rapid formation and extension of RCs induced by the occurrence of crystallization. Meeanwhile, simulation results indicate that stress distribution area decreases gradually and facilitate the formation of stress concentration, leading to the rapid extension of RCs and the occurrence of catastrophic fracture of MGs. In addition, MGs with sub-Tg, Tg ∼ Tx and above-Tx annealing not only exhibit such DBT in uniaxial compression, but also show a soft-hard transition in nanoindentation test. Graphical abstract: Image 1 Highlights: The dependence of ductile-brittle transition of MGs in multiaxial loading mode on thermal annealing was investigated through experiments and simulations. The annihilation of free volume and the reduction of released elastic energy dominate the evolution of shear bands of MGs in multiaxial loading mode. The evolution of shear bands is highly sensitive to structural relaxation of MGs in multiaxial loading mode.